Significance of questioning in nursing education – insights from neophyte students of nursing colleges in Islamabad and Peshawar - Muhammad Ishtiaq; Raisa Gul (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Questioning is a fundamental pedagogical approach essential for cultivating creativity, intellectual curiosity, and critical thinking skills. Its significance is particularly pronounced in healthcare education, where it substantially influences life-and-death decisions. This study examined novice undergraduate nursing students' perspectives on the efficacy of questioning in classrooms at three nursing colleges in Islamabad and Peshawar.METHODOLOGY: A descriptive qualitative study recruited twelve neophyte undergraduate nursing students from three nursing colleges using an extreme sampling strategy. The study duration was 6 months (May 2020 to October 2020). Teachers were approached to nominate the students who usually ask questions or do not ask questions. In-depth individualized interviews were conducted using a semi-structured interview guide by the primary researcher. Data was manually content analyzed. Ethical approval (Letter No 113-933-2020) and written informed was obtained.RESULTS: The interviews of twelve nursing students revealed several advantages of questioning in relation to enhancing learning, building confidence, and strengthening interpersonal relationships. They also envisioned the application of questioning strategy in their clinical practice. Students' and teachers’ training in asking and handling questioning is recommended respectively.CONCLUSION: Questioning is a fundamental skill that contributes to the holistic development of nursing students and prepares them for their roles in patient care and healthcare team collaboration. Nursing educators should prioritize the development of questioning ability among students, particularly those from backgrounds where rote learning is prevalent.